Methane emission reduction from large-bore natural gas two-stroke engines - Banji, Titilope Ibukun, author; Olsen, Daniel, advisor; Windom, Bret C., committee member; Wise, Dan, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2025)
Methane emissions from over 7000 large-bore natural gas engines used for gas compression in the United States result from combustion inefficiency and the escape of unburned methane through the crevices. Methane is a strong greenhouse gas with a warming potential 28 times that of carbon dioxide. The Inflation Reduction Act passed by the Biden administration in 2022 imposes a methane 'waste' fee that accumulates yearly to invest in clean energy and climate action starting in 2024. This study aims to reduce methane emissions from large-bore natural gas engines by utilizing fuel injection techniques, thereby advancing sustainable energy development. Natural gas primarily contains methane, and not all the methane from the engine fuel (natural gas) undergoes complete combustion in the engine cylinder. The inefficient combustion in large-bore engine cylinders has been associated with poor mixing within the cylinder at ignition. There have been efforts to enhance in-cylinder mixing in engines, and improved combustion variability and performance have validated the viability of improved in-cylinder mixing as a retrofit technology for these engines. Work aimed at enhancing mixing in the cylinders of large-bore engines has been conducted using experimental and numerical methods. Previous studies and experiments have established the potential for high-pressure fuel injection to improve in-cylinder mixing. This study addresses three key questions: how much pressure is sufficient to improve combustion efficiency through high-pressure fuel injection, how effective late-cycle high-pressure fuel injection is in reducing methane emissions, and what role the ring pack crevice volume plays in methane emissions from large-bore natural gas two-stroke engines. The engine modeled using CONVERGE Studio for CFD and tested for experimental studies was the large-bore 4-cylinder GMV 4TF engine. For the improved mixing and injection pressure sensitivity study, the model was simulated for four major sets of configured cases: baseline establishment, ideal mixing case development, injection pressure variation, and low-pressure, high-momentum cases. The results of this work demonstrate that improved mixing can potentially reduce methane emissions by half, and high-pressure fuel injection also enhances in-cylinder mixing in the main combustion chambers of large-bore engines. The optimal timing for the injection at different injection pressures was determined, and the limitations in each case were identified. It was concluded that fuel injection at 700 psi at -115 degrees BTDC gave the best mixing case. The level of mixing in low-pressure fuel injection systems was also found to be improved by having high-momentum fuel injection using increased flow areas at injection. The late-cycle high-pressure fuel injection and crevice volume study explored fuel injection pressure and timing optimization, crankcase methane emissions quantification and mitigation, ring-pack methane quantification, and the impact of the piston-cylinder crevice volume on methane emissions. While varying injection pressures and injection timing on the engine, the performance and methane emission characteristics were measured during experimental tests. Also, a model of the engine was created for computational fluid dynamics (CFD) simulations using CONVERGE Studio. Experimental results showed that methane emissions are minimized with late-cycle fuel injection at 500 psi and 100 degrees BTDC. Computational results showed that the ring pack contributes up to 34% of methane emissions in the large bore engine model. A last computational study also confirmed the flow of methane from the ring pack to the MCC and eventually out through the exhaust. This study showed that fuel injection conditions and the ring-pack crevice volume affect the mixing levels in the main combustion chamber of large-bore engines and directly impact the amount of methane emissions released through the exhaust.
Keywords: injection pressure; integral compressor; methane; injection timing; crevice volume; large-bore engines